2022
DOI: 10.1016/j.ajog.2020.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Low-molecular-weight heparin for prevention of preeclampsia and other placenta-mediated complications: a systematic review and meta-analysis

Abstract: BACKGROUND: Evidence on the impact of low-molecular-weight heparin, alone or in combination with low-dose aspirin, for the prevention for preeclampsia in high-risk patients is conflicting. OBJECTIVE: We conducted a meta-analysis of studies published to assess the effectiveness of low-molecular-weight heparin for the prevention of preeclampsia and other placenta-related complications in high-risk women. DATA SOURCES: A systematic search was performed to identify relevant studies, using the databases PubMed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 70 publications
0
27
0
4
Order By: Relevance
“…One meta-analyses found that the combination of LMWH and low-dose aspirin significantly reduced the risk of preeclampsia compared with low-dose aspirin alone. 106 Specific PAI-1 inhibitors have been developed to target high PAI-1 plasma levels but so far none are approved for therapeutic use in humans. 107 Further studies should be performed on PAI-1 plasma levels in a prospective design to determine the clinical relevance of high PAI-1 plasma levels in placenta-mediated pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
“…One meta-analyses found that the combination of LMWH and low-dose aspirin significantly reduced the risk of preeclampsia compared with low-dose aspirin alone. 106 Specific PAI-1 inhibitors have been developed to target high PAI-1 plasma levels but so far none are approved for therapeutic use in humans. 107 Further studies should be performed on PAI-1 plasma levels in a prospective design to determine the clinical relevance of high PAI-1 plasma levels in placenta-mediated pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have showed that aspirin treatment at 150 mg per day reduced preterm PE by 62% when compared to the placebo [ 172 ]. Low-dose aspirin is now recommended for PE prevention in high-risk women, although there is currently a dearth of conclusive evidence proving how aspirin treatment reduces prenatal morbidity and death [ 173 ]. Studies have also shown that, in high-risk women, the initiation of treatment with low-molecular-weight heparin before 16 weeks of gestation can significantly reduce the risk of PE and other placenta-mediated complications.…”
Section: Ferroptosis and Pe Therapymentioning
confidence: 99%
“…Die Datenlage zum potenziell präventiven Effekt von Heparin ist sehr heterogen, neueren Studienergebnissen zufolge könnte NMH einen günstigen Effekt in der Prävention der PE bzw. plazentamediierter Schwangerschaftskomplikationen zeigen [40,41]. Prinzipiell gilt auch die Anwendung von Heparin in der Schwangerschaft als sicher [1].…”
Section: Sekundärprävention -Aspirinunclassified